2016
DOI: 10.1097/ncc.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Young Adult Survivors of Childhood Brain Tumors

Abstract: Background To date there are few studies that examine the perspectives of older survivors of childhood brain tumors who are living with their families in terms of their sense of self and their role in their families. Objective To describe how adolescent and young adult survivors (AYA) of childhood brain tumors describe their HRQOL, that is their physical, emotional, and social functioning. Methods This qualitative descriptive study included a purposive sample of 41 AYA survivors of a childhood brain tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 43 publications
0
62
0
1
Order By: Relevance
“…Articles reported AYA survivors having impaired social functioning, expressed as, eg, avoiding social situations, or social isolation . Poorer social functioning was reported among brain tumour survivors compared with other cancer groups .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Articles reported AYA survivors having impaired social functioning, expressed as, eg, avoiding social situations, or social isolation . Poorer social functioning was reported among brain tumour survivors compared with other cancer groups .…”
Section: Resultsmentioning
confidence: 99%
“…Poorer social functioning was reported among brain tumour survivors compared with other cancer groups . Specifically, multiple studies reported a link between poorer social functioning and anticancer treatment and diagnosis . During treatment, survivors spend a long time in social isolation after which some young people found it difficult to engage with others again .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations